Development of Coffee Product Marketing System Through Branding and Use of E-Commerce in Wonosobo Village, Srono District, Banyuwangi Regency - G. Oka Warmana; Muhadjir Anwar; Fani Khoirotunnisa (Nusantara Science and Technology Proceedings, 2021)
Indonesia is one of the largest coffee-producing countries in the world. Indonesia has an advantage in terms of conditions related to natural resources. Diversification of coffee products can be developed on an SME scale as well as on a large scale, considering that coffee processing technology is relatively simple and can be designed on various business scales. One of the coffee industries is in Wonosobo Village, Srono District, Banyuwangi Regency, which is driven by An-Nuur Al-Fadhol, Islamic Boarding School students who process coffee plantations into packaged products. However, the business is still underdeveloped in terms of marketing distribution channels whose reach is still limited and packaging is relatively simple. This service activity seeks to provide knowledge transfer in the form of how to do product development and increase product diversity and diversification as well as how to packaging that has a certain appeal and branding to attract consumers and opportunities to be marketed to various regions through social networks and e-commerce facilities. Implementation method with: focus group discussion, demonstration, and practice or exercise. The result of this service activity is an increase in marketing activities that can increase sales and increase the efficiency of business activities with the application of management.